Effect of Glycine and Various Osmolarities of Culture Medium on In Vitro Development of Parthenogenesis and Somatic Cell Nuclear Transfer Embryos in Pigs - Joohyeong Lee; Yongjin Lee; Hae Hong Jun; Seung Tae Lee; Geun-Shik Lee; Eunsong Lee (The Korean Society of Animal Reproduction and Biotechnology, 2018)
The osmolarity of a medium that is commonly used for in vitro culture (IVC) of oocytes and embryos is lower than that of oviductal fluid in pigs. In vivo oocytes and embryos can resist high osmolarities to some extent due to the presence of organic osmolytes such as glycine and alanine. These amino acids act as a protective shield to maintain the shape and viability in high osmotic environments. The aim of this study was to determine the effects of glycine or/and alanine in medium with two different osmolarities (280 and 320 mOsm) during IVC on embryonic development after parthenogenesis (PA) and somatic cell nuclear transfer (SCNT) in pigs. To this end, IVC was divided into two stages; the 0-2 and 3-7 days of IVC. In each stage, embryos were cultured in medium with 280, 320, or 360 mOsm and their combinations with or without glycine or/and alanine according to the experimental design. Treatment groups were termed as, for example, "T(osmolarity of a medium used in 0-2 days of IVC)-(osmolarity of a medium used in 3-7 days of IVC)" T280-280 was served as control. When PA embryos were cultured in medium with various osmolarities, T320-280 showed a significantly higher blastocyst formation (29.0%) than control (22.2%) and T360-360 groups (6.9%). Glycine treatment in T320-280 significantly increased blastocyst formation (50.4%) compared to T320-280 only (36.5%) while no synergistic was observed after treatment with glycine and alanine together in T320-280 (45.7%). In contrast to PA embryonic development, the stimulating effect by the culture in T320-280 was not observed in SCNT blastocyst development (27.6% and 23.7% in T280-280 and T320-280, respectively) whereas the number of inner cell mass cells was significantly increased in T320-280 (6.1 cells vs. 9.6 cells). Glycine treatment significantly improved blastocyst formation of SCNT embryos in both T280-280 (27.6% vs. 38.0%) and T320-280 (23.7% vs. 35.3%). Our results demonstrate that IVC in T320-280 and treatment with glycine improves blastocyst formation of PA and SCNT embryos in pigs.